Functional and genetic epidemiological characterisation of the FFAR4 (GPR120) p.R270H variant in the Danish population. Issue 9 (11th April 2016) - Vestmar, Marie A; Andersson, Ehm A; Christensen, Charlotte R; Hauge, Maria; Glümer, Charlotte; Linneberg, Allan; Witte, Daniel R; Jørgensen, Marit E; Christensen, Cramer; Brandslund, Ivan; Lauritzen, Torsten; Pedersen, Oluf; et al.
Abstract : Background: p.R270H (rs116454156) in the long chain fatty acid 7TM receptor FFAR4 ( GPR120 ) which results in impaired Gαq (Gq) coupled signalling, has been associated with obesity. We aimed to extend the functional in vitro analyses of p.R270H and to investigate the association with obesity and glucose-related traits in the Danish population. Methods: Surface expression, Gq and Gi coupled signalling as well as β-arrestin recruitment were examined in vitro. p.R270H was genotyped using the exome chip array in 11 479 Danish adult individuals. Of these 4391 were obese and 4415 were normal weight. Association with quantitative metabolic traits comprised 8720 non-diabetic individuals. Results: p.R270H showed reduced surface expression of FFAR4. Ligand-independent activity was eliminated and strongly impaired through the Gq and Gi signalling pathways, respectively. The ligand-induced maximal signalling efficacy of p.R270H was reduced only through the Gq pathway. The p.R270H variant did not affect β-arrestin recruitment. p.R270H was not associated with increased risk of obesity nor increased fasting plasma glucose levels in the Danish study populations. Nor was it associated with these two traits in the European Network for Genetic and Genomic Epidemiology consortium data (N=34 901–71 175; p>0.70). It was also not associated with waist-hip ratio, glucose metabolism during an oral glucose tolerance test, lipid levels or with markers of adiposity (leptin, adiponectin), inflammation (high-sensitive C reactive protein; hs-CRP) and liver function (alanine aminotransferase) in the Danish population (p>0.05). Conclusions: We demonstrate that p.R270H of FFAR4 impairs Gq and Gi signalling of FFAR4 in vitro; however, this impaired signalling for p.R270H does not translate into associations with human metabolic phenotypes in the investigated populations.